2017
DOI: 10.1108/h-11-2016-0084
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between internal Shariah audit characteristics and its effectiveness

Abstract: Purpose This paper aims to examine the characteristics influencing internal Shariah audit effectiveness in Islamic financial institutions (IFIs) in Bahrain. Design/methodology/approach Data were collected from 76 internal Shariah auditors, 23 Shariah supervisory board and 16 audit and governance committee from 52 IFIs in Bahrain. The data were analyzed using structural equation method via SmartPLS 2.0 to examine the relationship between characteristics and effectiveness of internal Shariah audit. Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 18 publications
1
46
1
2
Order By: Relevance
“…Other studies define the effectiveness of internal Sharīʿah audit as the internal Sharīʿah auditors' capability of achieving IFIs' objectives, which can be obtained by improving their performance (Khalid et al, 2017).…”
Section: Internal Sharīʿah Audit Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies define the effectiveness of internal Sharīʿah audit as the internal Sharīʿah auditors' capability of achieving IFIs' objectives, which can be obtained by improving their performance (Khalid et al, 2017).…”
Section: Internal Sharīʿah Audit Effectivenessmentioning
confidence: 99%
“…To achieve internal Sharīʿah audit effectiveness, management's role does not stop at providing the required resources and human capital only. There is also need for management's commitment to implement the recommendations provided in the audit report to confirm the compatibility with Sharīʿah in all of the bank's activities (Khalid et al, 2017) Hence, it is anticipated that management support is an important factor in assuring the effectiveness of internal Sharīʿah audit in IBs.…”
Section: Internal Sharīʿah Audit Effectivenessmentioning
confidence: 99%
“…Furthermore, little research has examined the characteristics of IA in sharia financial institutions, although Khalid et al, (2017) tested the characteristics and performance of IA in Islamic financial institutions in Bahrain. Previous research related to CF has included a study by Violita & Handarbeni (2017), which pointed out the sharia compliance monitoring procedures in Islamic banks, and described the relationship between SSB and CF and IA in implementing sharia compliance monitoring.…”
Section: Consideringmentioning
confidence: 99%
“…Previous research has identified how to measure the effectiveness of the IA's and CF's roles (Alzeban, 2018;Khalid et al, 2017;Alzeban & Gwilliam, 2014) as organs of governance. Some characteristics which are commonly utilized include competence, work programs, and the number of members.…”
Section: Corporate Governance Mechanisms In Islamic Banking In Indonesiamentioning
confidence: 99%
See 1 more Smart Citation